2009
DOI: 10.1128/aem.01682-08
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dibenzothiophene Desulfurization in a Recombinant Pseudomonas putida Strain

Abstract: Biodesulfurization was monitored in a recombinant Pseudomonas putida CECT5279 strain. DszB desulfinase activity reached a sharp maximum at the early exponential phase, but it rapidly decreased at later growth phases. A model two-step resting-cell process combining sequentially P. putida cells from the late and early exponential growth phases was designed to significantly increase biodesulfurization.Biodesulfurization (BDS), based on the application of microorganisms that selectively remove sulfur atoms from or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Resting cells BDS assays were conducted using cells previously collected as commented above. In a previous work it was found that the enzymatic activity depends on the growth time: both monoxygenases (dszC and dszA) have a maximum of activity using cells of 23 h of growth time and the desulfinase (dszB) presents its maximum of activity using cells growth during 5 h. Therefore it was possible to optimise the biocatalyst formulation using mixtures of cells of these two different growth ages; the optimal formulation consists of a mixture of 0.7 g DCW L −1 of 5 h aged cells and 1.4 g DCW L −1 of cells with 23 h of growth time (total biomass concentration: 2.1 g L −1 ) and it is the biocatalyst used in this work.…”
Section: Methodsmentioning
confidence: 99%
“…Resting cells BDS assays were conducted using cells previously collected as commented above. In a previous work it was found that the enzymatic activity depends on the growth time: both monoxygenases (dszC and dszA) have a maximum of activity using cells of 23 h of growth time and the desulfinase (dszB) presents its maximum of activity using cells growth during 5 h. Therefore it was possible to optimise the biocatalyst formulation using mixtures of cells of these two different growth ages; the optimal formulation consists of a mixture of 0.7 g DCW L −1 of 5 h aged cells and 1.4 g DCW L −1 of cells with 23 h of growth time (total biomass concentration: 2.1 g L −1 ) and it is the biocatalyst used in this work.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the strain was used as a model system for horizontal and vertical evolution of catabolic pathways in the degradation of alkylaromatic compounds (Ramos et al ., 1986; 1987; Timmis, ; Li et al ., ). The genetic versatility of this bacterium has been proven to be large, making it suitable for metabolic engineering to create superior strains for a variety of biotechnological applications, including the design of new catabolic pathways for pollutants, the biocatalysis of pharmaceutical intermediates and quality improvement of fossil fuels (Calzada et al ., ; Prakash et al ., ; Tao et al ., ; Fernández et al ., ). For P. putida there are 12 complete and 18 in‐progress genomes publicly available on NCBI (http://www.ncbi.nlm.nih.gov/genome/genomes/174, as of June 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Dibenzothiophene has been widely used as a model compound of the polycyclic organic sulphur components of fossil fuels (Calzada et al , 2009). Organic sulphur is characterized by covalent C–S bonds and can be regarded as an element that is integrated into the macromolecular matrix of coal and in organic sulphur compounds present in oil (Klein et al , 1994).…”
Section: Introductionmentioning
confidence: 99%